Explication: Method and Form - Bielik, Lukáš (Teorie vědy / Theory of Science, 2015)
Explication belongs among the core methods of analytic philosophy. In the paper I propose to distinguish explicitely between the method of explication and its outcome. Building on the explication project of Rudolf Carnap, I attempt to elaborate upon his work. I point out the open issues arising from Carnap’s criteria of adequate explication. I present the aspects in which explications differ from definitions, a logical form of explications as well as the explicit steps that are characteristic for the method of explication. Finally, I consider reasons to conceive explication (in the sense of a product of explicating) to be a relation between meaning characterization and an appropriate definition.